Journalist Neal Spelce describes the response to his live report on the Texas Tower shooting of 1966 - Spelce, Neal; Wallenfeldt, Jeffrey H.; Encyclopaedia Britannica, Inc. (Chicago, IL : Encyclopedia Britannica, 2016)
Neal Spelce interview: Was there any frame of reference to which to compare the Texas Tower shooting of 1966 as it was happening?
Title from resource description page (viewed February 4, 2022).
In English.
Keywords: University of Texas at Austin -- History; University of Texas at Austin; School shootings -- Texas -- Austin -- 20th century; Mass murder -- Texas -- Austin -- 20th century; Meurtre multiple dans les écoles -- Texas -- Austin -- 20e siècle.; Meurtre multiple -- Texas -- Austin -- 20e siècle.; Mass murder; School shootings; Texas -- Austin; 1900-1999; Interview; interviews; History; Interviews; Interviews; Interviews